KARAKTERISTIK MINERAL LEMPUNG PADA SEDIMEN RESEN PERMUKAAN DASAR LAUT DI PERAIRAN KOTA SEMARANG - K. Budiono; Hermes Panggabean (Pusat Survei Geologi, 2008)
Clay mineral is a group of mineral which suplay more than 16% of sediments distribution in the earth surface. The clay mineral can be occurred both on the land and sea bottom. The clay mineral which is deposited in the coastal and sea bottom have a unique mechanism, and consequently creates many kind of clay mineral where this conditions is influenced by the deph, temperature, light, topography and organism.The study of clay mineral distribution in the coastal and Â marine sediments enables to analysis the sedimentation processes, where the occurrence of this mineral is influenced by the origin of the sediments. Generally, the surficial sediments of Semarang offshore is consists of clay and silt.Based on the SEM analysis the clay mineral in Semarang offshore is dominated by caolinite, illite and mixed layer of montmorilonite and illite.Keywords: offshore surficial sediments, clay mineral, sedimentation process